Religious Coaching and Mental Health: Case Study at MAN Indragiri Hilir - Gaffar, Marwan; Raja Ahmad, Raja Rahima Munawarah; Zaitun, Zaitun; Zein, Nurhayati; Kasmiati, Kasmiati; Thahir, Musa (Universitas Malikussaleh, 2020)
This research is motivated by the mental inadequacies of students who can hinder the goals of education and teaching in the school environment. Therefore, mental health guidance is needed through religious formation. Based on these phenomena, this study aims: 1) to find out the efforts made by teachers in developing religious and mental health of students in MAN Indragiri Hilir; and 2) to analyze the presence or absence of the influence of religious guidance on the mental health of students in MAN Indragiri Hilir. The research method used was a quantitative study conducted on 56 students. Data collected through observation, interviews and questionnaires. After the data is collected completely, a data analysis is done using a simple linear regression test with the help of SPSS version 23.00 for Windows. The results obtained from this study include: 1) religious guidance conducted by teachers in mentally developing students, including: habituation of Dhuha prayer, Dhuhr prayer in congregation, reading Asmaul Husna and giving Jariyah every Friday in each class. While activities outside of effective learning hours include social service and apostolic assembly; and 2) there is an influence of religious guidance on the mental health of students by 53.7% on mental health in MAN 2 Indragiri Hilir